Long-Term Follow-Up after Treatment of Cryptorchidism - Thorup, Jorgen; Cortes, Dina (European Journal of Pediatric Surgery, 2016)
When considering long-term prognosis and results in adult age following treatment of cryptorchidism in childhood there are three main issues to be discussed: cosmetics, fertility, and malignancy. In the present review, the most recent research on the topics related to summaries of well-known knowledge on the field is presented.To some extent a smaller testis in a higher scrotal position than normal must be accepted as a fair cosmetic result after orchidopexy in childhood. The smaller testis size is related to the impaired fertility potential of the testis. In cases with atrophy, testicular prosthesis implantation is an option with good operative results. The risk of impaired fertility potential in adults treated in childhood for cryptorchidism is still significant and worst in bilateral disease. We need repetitive solid long-term follow-up data to show that orchidopexy performed within first year of life has markedly improved the fertility potential. Men previously having orchidopexy for cryptorchidism related to intra-abdominal testes, abnormal external genitalia and/or abnormal karyotype, and/or hypospadias are of special increased risk of developing testicular cancer. In these cases intratubular germ cell neoplasia may be diagnosed in prepubertal age. Early orchidopexy may lower the risk of developing testicular cancer.
Keywords: cryptorchidism; testis; fertility; testicular cancer